2022
DOI: 10.1021/acsanm.2c04789
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Metal–Alloy Interface in RuNi Nanoplates Boosts Highly Efficient Hydrogen Electrocatalysis

Abstract: Designing a unique metastable interface provides a promising way to achieve high catalytic performance yet remains a great challenge due to the thermodynamics’ unstable nature. In this work, we constructed the stabilized metastable interface between metastable ruthenium–nickel alloy and metastable hexagonal–close-packed nickel via a one-step solvothermal method. The optimized nanocatalyst (denoted as hcp RuNi) shows bifunctional performance toward electrochemical hydrogen oxidation and evolution reactions (HOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Additionally, we found that Ru/Cu−Cu 2 O@C held the strongest OH* adsorption among the four catalysts. Such an enhanced OH* adsorptive behavior favored the capture of OH* species on the Cu 2 O surface, in accord with the CO stripping results (Figure 6g and Figure S20) [47] . Since the dissociation of water was a primary step that directly determined the HER activity, we also calculated the adsorption free energies of H 2 O* for the four catalysts (Figure 6h and Figure S21).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, we found that Ru/Cu−Cu 2 O@C held the strongest OH* adsorption among the four catalysts. Such an enhanced OH* adsorptive behavior favored the capture of OH* species on the Cu 2 O surface, in accord with the CO stripping results (Figure 6g and Figure S20) [47] . Since the dissociation of water was a primary step that directly determined the HER activity, we also calculated the adsorption free energies of H 2 O* for the four catalysts (Figure 6h and Figure S21).…”
Section: Resultssupporting
confidence: 78%
“…Such an enhanced OH* adsorptive behavior favored the capture of OH* species on the Cu 2 O surface, in accord with the CO stripping results (Figure 6g and Figure S20). [47] Since the dissociation of water was a primary step that directly determined the HER activity, we also calculated the adsorption free energies of H 2 O* for the four catalysts (Figure 6h and Figure S21). The values of adsorption energies of ΔG H 2 O * on Ru/CuÀ Cu 2 O@C, CuÀ Cu 2 O@C, Ru/Cu 2 O@C and Ru/Cu@C were À 0.38, À 0.21, À 0.24 and À 0.20 eV, respectively.…”
Section: Chemsuschemmentioning
confidence: 99%
“…However, once H ads and OH – are adsorbed together, they are likely to recombine into H 2 O at the active site, hindering the production of H 2 . Previously, Fang et al proposed that RuNi shows excellent HER/HOR performance because of more oxophilic sites located on the Ni atoms, which facilitate the adsorption of OH – . A similar two-site mechanism might be fit for our catalyst, that is, Ni anchors the OH – and leads to accelerated dissociation of water.…”
Section: Resultsmentioning
confidence: 65%
“…55 proposed that RuNi shows excellent HER/HOR performance because of more oxophilic sites located on the Ni atoms, which facilitate the adsorption of OH − . 56 A similar two-site mechanism might be fit for our catalyst, 57−59 that is, Ni anchors the OH − and leads to accelerated dissociation of water. To confirm this, the results of the CO stripping also investigate the adsorption of OH − on the catalyst.…”
Section: Resultsmentioning
confidence: 76%
“…[5] In previous simulation works, researchers have referred to the interface structure with the lowest interfacial energy as stable interface structure, while the interface models with higher interfacial energies are termed as metastable interface structures. [6][7][8] Stable interface structure is simple and unique, while metastable interface structures are widely present in composite materials, exhibiting diversity and complexity. [9,10] Therefore, conducting in-depth research on metastable interface structures holds significant importance for the design of interface materials.…”
Section: Introductionmentioning
confidence: 99%